2020
DOI: 10.1007/s00167-020-06119-w
|View full text |Cite|
|
Sign up to set email alerts
|

Anterolateral ligament reconstruction improves the clinical and functional outcomes of anterior cruciate ligament reconstruction in athletes

Abstract: Purpose To compare the outcomes of anterior cruciate ligament (ACL) reconstruction with those of combined ACL and anterolateral ligament (ALL) reconstruction in ACL-deicient knees. The objective of this study was to improve knowledge regarding the treatment of ACL-deicient knees with combined ACL and ALL reconstruction. Combined ACL and ALL reconstruction has been hypothesized to result in better clinical and functional outcomes than isolated ACL reconstruction (ACLR). Methods One-hundred and seven adult male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 40 publications
2
61
0
1
Order By: Relevance
“…Hamido et al. 34 randomized 107 male athletes and reported reduced instrumented knee laxity and a lower rate of graft failure with the added anterolateral ligament reconstruction at 60 months’ follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamido et al. 34 randomized 107 male athletes and reported reduced instrumented knee laxity and a lower rate of graft failure with the added anterolateral ligament reconstruction at 60 months’ follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…A further 3 RCTs compared the combined anterolateral ligament reconstruction with ACLR compared with ACLR alone, with 1 trial reporting significant differences. Hamido et al 34 randomized 107 male athletes and reported reduced instrumented knee laxity and a lower rate of graft failure with the added anterolateral ligament reconstruction at 60 months' follow-up.…”
Section: Additional Proceduresmentioning
confidence: 99%
“…Indeed, the Stability study 40 has shown that adding a LEAT to an anatomical ACL reconstruction reduces the risk of clinical failure by 38% and graft rupture by 67% as compared with ACL reconstruction alone. In line with the renewed interest in LEAT, clinical studies [41][42][43][44] have reported the results of combined ACL and ALLR, suggesting superior outcomes when compared with ACL reconstruction alone. In patients displaying high-grade pivot-shift, the addition of LEAT 45 46 or ALLR 47 48 seem to result in significant improvement in controlling rotational laxity.…”
Section: Editorialmentioning
confidence: 92%
“…Previous biomechanical studies have shown that the addition of ALL reconstruction to ACL reconstruction for ACL and ALL deficient knees improves rotational instability [ 22 , 31 ]. Moreover, combined ACL and ALL reconstruction has been reported as an effective approach for lowering the rate of graft failure when compared to ACL reconstruction alone [ 8 , 10 , 27 ]. Double-bundle ACL reconstruction has been also reported to be associated with superior knee stability (both anterior and rotational stability) than single-bundle reconstruction, while subjective scorings have showed no statistical differences [ 18 ].…”
Section: Introductionmentioning
confidence: 99%